ECONOMIC VALUATION OF THE MANGROVE ECOSYSTEM IN RAWA MEKAR JAYA VILLAGE, SUNGAI APIT DISTRICT, SIAK REGENCY - Saprianto, Saprianto; Warningsih, Trisla; Bathara, Lamun (Asian Journal of Aquatic Sciences, 2022)
This study aims to describe the characteristics of the mangrove forest ecosystem and analyze the direct benefits of the mangrove ecosystem in Rawa Mekar Jaya Village, Sungai Apit District, Siak Regency. The method used in this study is a survey method, namely by conducting field observations and direct interviews with respondents, where the sampling technique found uses Non-Probability techniques or is determined by the researchers themselves or according to expert considerations with a total of 42 respondents. This shows that the tree-level mangrove community structure in the mangrove area, namely Rhizophora apiculata is the dominant tree species with a tree density of 30,617.2 trees/ha, then Rhizophora stylosa 9,629.63 trees/ha, Avicennia alba 8,333.33 trees/ha, and Ceriops tagal 777.78 trees/ha. Furthermore, a number of villagers from Rawa Mekar Jaya have made direct use of mangroves in the form of fish for Rp. 402,000,000/year, catching shrimp for around Rp. 21,600,000/year and taking honey for Rp. 28,800,000/year. The total economic gain of IDR 4.345,000,000/year shows that mangrove extension is very important for the people of Rawa Mekar Jaya village, both direct and indirect benefits.